Helal and Weil osteotomy in the treatment of metatarsalgia in the conditions of the transverse deformity forefoot - Prozorovskiy, Dmytro; Buznytskiy, Ruslan (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Transverse-spread deformity of the forefoot with hallux valgus is found in 75 % of women in the population. At the same time, structural and functional changes in the foot lead to redistribution of load during walking between the heads of the metatarsal bones and the occurrence of metatarsalgia. Objective. To conduct a comparative analysis of the results of surgical treatment of metatarsalgia in patients with transverse-spread deformity of the forefoot after performing corrective osteotomies Helal and Weil. Methods. The study is based on the surgical treatment of 42 (64 feet) patients with metatarsalgia due to transverse deformity of the forefoot. Patients were divided into two groups depending on the surgical method of eliminating metatarsalgia: in the first performed an osteotomy Helal (32 cases), in the second — Weil (32). The mean follow-up of patients in the first group was 19.8 months, the second — 21.5 months. Results. According to the assessment of AOFAS scale, the result of treatment of metatarsalgia and transverse deformity of the forefoot in patients of the first group was 89.4 points, the second — 83.1 points. Regression of metatarsalgia in patients of the first group was recorded in 29 (90.6 %) cases, the second — in 26 (81.3 %) (criterion χ2 = 1.16; p = 0.28). Recurrences of metatarsalgia were observed in patients after the use of both Helal and Weil osteotomies and accounted for 6.3 and 9.4 % of cases, respectively. The occurrence of transfer metatarsalgia of the anterior foot was registered in 3.1 % of cases after Helal osteotomy, in 9.4 % — Weil osteotomy. Conclusions. Surgical treatment of metatarsalgia caused by transverse deformity of the forefoot with the use of corrective osteotomies Helal and Weil allowed to achieve positive results in 90.6 and 81.3 % of cases, respectively. These surgical techniques can be successfully used for the treatment of metatarsalgia of the forefoot with a violation of the metatarsal parabola.